2012
DOI: 10.1021/ie3013506
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Spent Pot-lining with Aluminum Anodizing Wastewaters: Selective Precipitation of Aluminum and Fluoride as an Aluminum Hydroxyfluoride Hydrate Product

Abstract: Wastewaters generated by the aluminum anodizing industry have been identified as a source of acid, Al 3+ , and caustic values that could be used for the treatment of spent pot-lining (SPL) generated in primary aluminum smelting. In this paper, recovery of aluminum and fluoride values as an aluminum fluoride product that could be converted into smelter grade (SG) AlF 3 for recycling in aluminum smelting is reported. Experimental observations were contrasted with a thermodynamic model of the solution equilibria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 9 publications
(34 reference statements)
2
5
0
Order By: Relevance
“…Fig. 4) suggested that AlF 3 (s), NaAl 3 F 6 (s) were unlikely to form, recently published solubility constants for the AlF 2 OH(s) phase 14,40 matched the low soluble Al values measured from gibbsite suspensions, as shown in Fig. 4.…”
Section: Resultssupporting
confidence: 70%
“…Fig. 4) suggested that AlF 3 (s), NaAl 3 F 6 (s) were unlikely to form, recently published solubility constants for the AlF 2 OH(s) phase 14,40 matched the low soluble Al values measured from gibbsite suspensions, as shown in Fig. 4.…”
Section: Resultssupporting
confidence: 70%
“…It suggests that AlF2 + may be converting to AlF2OH, and this has been previously suggested by (Lisbona, 2012b) according to Equation 5.1.…”
Section: Preliminary Speciation Modellingsupporting
confidence: 52%
“…The response experimental results based on BBD are listed in Table 6. The comparison and analysis of models 15,24,25 No. Equation…”
Section: Model Fitting and Anovamentioning
confidence: 99%